Topological bounded corner states induced by long-range interactions in Kagome lattice. (17th December 2020) - Li, Yu-Zeng; Liu, Zheng-Fang; Xu, Xun-Wei; Wu, Qing-Ping; Xiao, Xian-Bo; Liu, Mei-Rong; Chang, Lu-Lu; Zhang, Ruo-Long
Abstract: We theoretically studied the corner states in photonic Kagome lattice with long-range interactions. Literature has confirmed that such model supports zero-energy corner states and finite-energy corner states known as type-II corner states. In this paper, through careful research, we found that there is another new type of finite-energy corner state in this system. By using the approximation method, we realized that the addition of long-range interactions causes coupling between topological edge states, which in turn makes these finite-energy corner states split from the edge states. Moreover, these finite-energy corner states are not located on the corners, but around the corners. And they are immune to the disorder in coupling strengths. Thus we call them topological bounded corner states. Our work reveals a way to generate bounded corner states by the long-range interactions, which offers a way for designing novel bounded devices.